Sex Differences in Exercise-Training-Related Functional and Morphological Adaptation of Rat Gracilis Muscle Arterioles - Merkely, Petra; Bakos, Marcell; Bányai, Bálint; Monori-Kiss, Anna; Horváth, Eszter M.; Bognár, Judit; Benkő, Rita; Oláh, Attila; Radovits, Tamás; Merkely, Béla; Ács, Nándor; Nádasy, György L.; et al. (Frontiers in Physiology, 2021)
Background: The cardiovascular effects of training have been widely investigated; however, few studies have addressed sex differences in arteriolar adaptation. In the current study, we examined the adaptation of the gracilis arterioles of male and female rats in response to intensive training. Methods: Wistar rats were divided into four groups: male exercise (ME) and female exercise (FE) animals that underwent a 12-week intensive swim-training program (5 days/week, 200 min/day); and male control (MC) and female control (FC) animals that were placed in water for 5 min daily. Exercise-induced cardiac hypertrophy was confirmed by echocardiography. Following training, the gracilis muscle arterioles were prepared, and their biomechanical properties and functional reactivity were tested using pressure arteriography. Collagen and smooth muscle remodeling were observed in the histological sections. Results: Left ventricular mass was elevated in both sexes in response to chronic training. In the gracilis arterioles, the inner radius and wall tension increased in female animals, and the wall thickness and elastic modulus were reduced in males. Myogenic tone was reduced in the ME group, whereas norepinephrine-induced vasoconstriction was elevated in the FE group. More pronounced collagen staining was observed in the ME group than in the MC group. Relative hypertrophy and tangential stress of the gracilis arterioles were higher in females than in males. The direct vasoconstriction induced by testosterone was lower in females, and was reduced as an effect of exercise in males. Conclusion: The gracilis muscle arteriole was remodeled as a result of swim-training, and this adaptation was sex-dependent.